Multi-Modal Multi-Spectral Intravital Microscopic Imaging of Signaling Dynamics in Real-Time during Tumor–Immune Interactions - Tracy W. Liu; Seth T. Gammon; David Piwnica-Worms (Cells, 2021)
Intravital microscopic imaging (IVM) allows for the study of interactions between immune cells and tumor cells in a dynamic, physiologically relevant system in vivo. Current IVM strategies primarily use fluorescence imaging; however, with the advances in bioluminescence imaging and the development of new bioluminescent reporters with expanded emission spectra, the applications for bioluminescence are extending to single cell imaging. Herein, we describe a molecular imaging window chamber platform that uniquely combines both bioluminescent and fluorescent genetically encoded reporters, as well as exogenous reporters, providing a powerful multi-plex strategy to study molecular and cellular processes in real-time in intact living systems at single cell resolution all in one system. We demonstrate that our molecular imaging window chamber platform is capable of imaging signaling dynamics in real-time at cellular resolution during tumor progression. Importantly, we expand the utility of IVM by modifying an off-the-shelf commercial system with the addition of bioluminescence imaging achieved by the addition of a CCD camera and demonstrate high quality imaging within the reaches of any biology laboratory.